STRATEGI SALES DAN MARKETING DALAM MENINGKATKAN PENDAPATAN DAN CUSTOMER RELATIONSHIP MANAGEMENT DALAM INDUSTRI PERHOTELAN - Evert, Ferenc Devlin; Ekadjaja, Margarita (Jurnal Serina Abdimas, 2024)
Hotels are a means of lodging for anyone who needs a temporary place to rest. In a hotel there must be a sales and marketing team whose job is to find and maintain the loyalty of its customers. This internship activity is one of the Community Service (PKM) programs at Hotel Ciputra Jakarta which really pays attention to professionalism and maintaining relationships with customers so that customers feel satisfied with the service they receive. However, considering the lack of workers in the sales admin & marketing department, Hotel Ciputra Jakarta is willing to collaborate with FEB UNTAR by providing opportunities for students majoring in management at FEB UNTAR to do internships at Hotel Ciputra Jakarta. The aim of this internship activity is that apart from earning additional income, FEB UNTAR students can learn sales and marketing strategies in increasing hotel revenues as well as relationship management with customers which many people call the spearhead of the hotel itself. The PKM program is implemented offline by going directly into the field. The implementation method to expand intern students' knowledge about sales and marketing is by going directly and observing within the sales and marketing department as well as direct interviews with the sales and marketing staff who carry out these activities. The results of this activity lasted very well for six months and concluded that sales and marketing were very influential in increasing revenue and good relations with customers with the various strategies they implemented. As a suggestion proposed to partners, partners can enrich innovation in reaching and maintaining good relationship management with customers so that they can be an advantage over other competitors.